Strategi Kepala Sekolah dalam Menjalin Hubungan Kerjasama dengan Dunia Usaha Otomotif di SMK Sunan Drajat Lamongan - Muh. Hasyim Rosyidi; Nasikhun Amin (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2022)
The principal's strategy is to establish a cooperative relationship with the automotive business world at SMK Sunan Drajat Lamongan. Planning a strategic cooperation in the automotive business world first to analyze the impact experienced later in order to achieve an effective and efficient goal. The purpose of this study is to, 1) Knowing the strategy of the principal of SMK Sunan Drajat Lamongan in a cooperative relationship with the automotive business world. 2) Knowing the supporting factors and inhibiting factors in the implementation of the principal's cooperation strategy with the automotive business world. This study uses a descriptive qualitative research using three stages, namely. : First, dig up research data. The second stage is to analyze the data that has been obtained. The third stage is to check the validity of the data. The results of the research carried out show the conclusions, namely, First, the principal makes a plan for the strategy to be implemented by creating a team and analyzing the impact that will be experienced during the implementation of the collaboration process. Second, determine the steps of the cooperation strategy and prepare the facilities and infrastructure to support the practice of field work as well as a condition for achieving the strategic process of cooperation with the automotive business world. Third, evaluate the implementation of the cooperation strategy by making a questionnaire every month to be filled in so that it is easy in terms of supervision, coordination and good communication and field surveys are carried out in order to know the stages of the implementation of the cooperation strategy. 2) The supporting factors and inhibiting factors for implementing the principal's cooperation strategy are facilities and infrastructure as well as the policies and wishes of the boarding school caregivers. The inhibiting factors for implementing the cooperative strategy include equating the mindset of Islamic boarding school human resources with the business/industry world and the application of an inappropriate curriculum also becomes an obstacle in learning.